2022
DOI: 10.1021/acs.jpcb.1c09423
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change from U- to I-Shape of Ion Transporters Facilitates K+ Transport across Lipid Bilayers

Abstract: We have investigated, at the atomic level, the ion-fishing mechanism underlying the ion transport across membranes mediated by an artificial ion transporter composed of a hydroxyl-rich cholesterol group, a flexible alkyl chain, and a crown ether. Our results show that the transporter can spontaneously insert into the membrane and switch between the folded (U-shaped) and extended (I-shaped) conformations. The free-energy profile associated with the conformational transition indicates that compared with the U-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…90 The multistep catch-and-release ion-fishing cycle was originally envisioned by us and later exactly reproduced by Shao and Cai using a molecular dynamics simulation approach. 91 Among eight MFs studied, except for MF5-C14 that is weakly Na +selective, the remaining seven MFs all are K + -selective, with MF6-C8 and MF6-C14 exhibiting the highest K + transport activity (EC 50 = 0.37 mol% relative to the lipids) and the highest K + /Na + selectivity of 18.3, respectively. It is interesting to note that all MFs do not transport Li + ions and that ion transport efficiencies of molecular ion fishers MFs generally are not as good as molecular swings MSs.…”
Section: Unconventional Membrane Transportersmentioning
confidence: 89%
“…90 The multistep catch-and-release ion-fishing cycle was originally envisioned by us and later exactly reproduced by Shao and Cai using a molecular dynamics simulation approach. 91 Among eight MFs studied, except for MF5-C14 that is weakly Na +selective, the remaining seven MFs all are K + -selective, with MF6-C8 and MF6-C14 exhibiting the highest K + transport activity (EC 50 = 0.37 mol% relative to the lipids) and the highest K + /Na + selectivity of 18.3, respectively. It is interesting to note that all MFs do not transport Li + ions and that ion transport efficiencies of molecular ion fishers MFs generally are not as good as molecular swings MSs.…”
Section: Unconventional Membrane Transportersmentioning
confidence: 89%
“…Miao, Shao, and Cai used MD simulations to study an ion transporter consisting of a single molecule spanning the lipid bilayer. 285 MD simulations show that the artificial transporter translocates K + ions through alternating U-shape and linear shapes. The free energy of the transporter conformation in the membrane was then calculated using MD simulations.…”
Section: Drug-membrane Interactionsmentioning
confidence: 99%
“…MD simulations were used to model the assembly and ligand binding to the polymer ion channel. Miao, Shao, and Cai used MD simulations to study an ion transporter consisting of a single molecule spanning the lipid bilayer . MD simulations show that the artificial transporter translocates K + ions through alternating U-shape and linear shapes.…”
Section: Drug-membrane Interactionsmentioning
confidence: 99%
“…100,102 A computational study found that Hbonding between the cholesterol and the phosphate of a lipid restricted lateral translocation, rationalizing the efficiency of this anchor group. 103 Interestingly, after prolonged investigations, no single-channel current traces were obtained for the moncholesterol 16 or a bis-cholesterol anchored system in BLM conductance experiments, indicating that ions were not transported through well-defined channels. 99,102 Ill-defined and transient single-channel current traces were observed for the molecular swing transporter 17 in BLM experiments.…”
Section: ■ Anchored Ion Carriersmentioning
confidence: 99%
“…Zeng and co-workers have been pioneers in this area, developing transport system 16 (Figure ), a so-called “molecular ion fisher.” The cholesterol unit was used to anchor the system, while the flexible linker to the benzo-18-crown-6 K + binding motif facilitated transport by this unconventional mechanism . Transporters with different anchoring architectures have been reported, based on a single cholesterol lock, as well as systems with a membrane-spanning cross-beam containing two cholesterol units 17 . , A computational study found that H-bonding between the cholesterol and the phosphate of a lipid restricted lateral translocation, rationalizing the efficiency of this anchor group . Interestingly, after prolonged investigations, no single-channel current traces were obtained for the moncholesterol 16 or a bis-cholesterol anchored system in BLM conductance experiments, indicating that ions were not transported through well-defined channels. , Ill-defined and transient single-channel current traces were observed for the molecular swing transporter 17 in BLM experiments .…”
Section: Anchored Ion Carriersmentioning
confidence: 99%